Self-Treatment Methods for Livestock—Backrubbers - Emma N. I. Weeks; Phillip E. Kaufman (EDIS)
Back rubbers are a method of pesticide self-treatment for cattle. When bothered by insects or other pests, cattle tend to rub against objects. Backrubbers provide a rubbing surface that is treated with a pesticide. Cattle self-treat during rubbing, which reduces the number of flies, particularly horn flies, and parasites such as lice, on the animal. Backrubbers may be purchased commercially or constructed from easily available materials. A properly designed backrubber that supplies pesticide reliably to the animal can be a valuable addition to an integrated pest management program. This revised 4-page fact sheet was written by E. N. I. Weeks and P. E. Kaufman, and published by the UF Department of Entomology and Nematology, September 2012.